2016
DOI: 10.15252/emmm.201505480
|View full text |Cite
|
Sign up to set email alerts
|

Targeting netrin‐1/DCC interaction in diffuse large B‐cell and mantle cell lymphomas

Abstract: DCC (Deleted in Colorectal Carcinoma) has been demonstrated to constrain tumor progression by inducing apoptosis unless engaged by its ligand netrin‐1. This has been shown in breast and colorectal cancers; however, this tumor suppressive function in other cancers is not established. Using a transgenic mouse model, we report here that inhibition of DCC‐induced apoptosis is associated with lymphomagenesis. In human diffuse large B‐cell lymphoma (DLBCL), an imbalance of the netrin‐1/DCC ratio suggests a loss of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 31 publications
(46 reference statements)
1
29
0
2
Order By: Relevance
“…Indeed, targeted deletion of Gremlin 1 in mice leads to a loss of kidneys due to complete elimination of the metanephric mesenchyme by apoptosis (Michos et al, ). Recently, we demonstrated protective effects of variant rs1880646, which is located in NTN1 (Netrin 1), a gene associated with apoptotic phenotypes (Broutier et al, ; Lahlali et al, ), with NSCL±P in this same Brazilian sample (Machado et al, ). Together GREM1 and NTN1 SNP may interact, reducing NSCL±P risk.…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations
“…Indeed, targeted deletion of Gremlin 1 in mice leads to a loss of kidneys due to complete elimination of the metanephric mesenchyme by apoptosis (Michos et al, ). Recently, we demonstrated protective effects of variant rs1880646, which is located in NTN1 (Netrin 1), a gene associated with apoptotic phenotypes (Broutier et al, ; Lahlali et al, ), with NSCL±P in this same Brazilian sample (Machado et al, ). Together GREM1 and NTN1 SNP may interact, reducing NSCL±P risk.…”
Section: Introductionmentioning
confidence: 61%
“…Recently, we demonstrated protective effects of variant rs1880646, which is located in NTN1 (Netrin 1), a gene associated with apoptotic phenotypes (Broutier et al, 2016;Lahlali et al, 2016), with NSCLAEP in this same Brazilian sample . Together GREM1 and NTN1 SNP may interact, reducing NSCLAEP risk.…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…These should be confirmed in larger series. Recently, Broutier et al () confirmed a tumour suppressor role for DCC in diffuse large B‐cell lymphoma (DLBCL). They demonstrated that an imbalance in the netrin‐1 (NTN1)/DCC expression ratio is associated with aggressive lymphoma, and DCC loss occurs in germinal centre DLBCL.…”
mentioning
confidence: 98%